Exploring substrate–microbe interactions: a metabiotic approach toward developing targeted synbiotic compositions - Bodo Speckmann; Ellen Ehring; Jiaying Hu; Ana Rodriguez Mateos (Gut Microbes, 2024)
ABSTRACTGut microbiota is an important modulator of human health and contributes to high inter-individual variation in response to food and pharmaceutical ingredients. The clinical outcomes of interventions with prebiotics, probiotics, and synbiotics have been mixed and often unpredictable, arguing for novel approaches for developing microbiome-targeted therapeutics. Here, we review how the gut microbiota determines the fate of and individual responses to dietary and xenobiotic compounds via its immense metabolic potential. We highlight that microbial metabolites play a crucial role as targetable mediators in the microbiota-host health relationship. With this in mind, we expand the concept of synbiotics beyond prebiotics’ role in facilitating growth and engraftment of probiotics, by focusing on microbial metabolism as a vital mode of action thereof. Consequently, we discuss synbiotic compositions that enable the guided metabolism of dietary or co-formulated ingredients by specific microbes leading to target molecules with beneficial functions. A workflow to develop novel synbiotics is presented, including the selection of promising target metabolites (e.g. equol, urolithin A, spermidine, indole-3 derivatives), identification of suitable substrates and producer strains applying bioinformatic tools, gut models, and eventually human trials.In conclusion, we propose that discovering and enabling specific substrate–microbe interactions is a valuable strategy to rationally design synbiotics that could establish a new category of hybrid nutra-/pharmaceuticals.